Islanding operation of hybrid micro-grid system with power management control scheme - Ambia, M.; Al-Durra, A.; Caruana, C.; Muyeen, S.M. (2012)
In this paper, islanding operation of a hybrid micro-grid system is proposed with power management control scheme. When micro-grid system undergoes transition from grid connected to the islanded mode, it is required for the ac-dc based micro-grid system to provide adequate power to ac and dc loads connected in the system. Even when utility grid is disconnected from the micro-grid system, there is possibility of power imbalance in the system which may result in system instability. In this paper, control strategy of voltage source converter is presented which can maintain the terminal voltage of the micro-grid system constant during both grid connected and islanded modes. Another salient feature is the incorporation of power management control scheme which ensures the power management in the ac-dc based micro-grid system when it switches from grid connected to islanded mode or islanded mode to grid reconnected mode. The simulation results from PSCAD/EMTDC show that the micro-grid system may lose its stable operation without power management control scheme during islanded mode even if the voltage source converter is connected to the system. The effectiveness of the proposed control strategy is verified under three different scenarios.